Breaking the path of institutional development?: alternatives to the new determinism - Crouch, Colin,Farrell, Henry (online, 2002)
Abstract:
urn:nbn:de:101:1-2019072514123787375707
Keywords: (stw)Institutioneller Wandel; (stw)Pfadabhängigkeit; (stw)Bayes-Statistik; (stw)Theorie; (stw)Politische Entscheidung; (thesoz)Institution; (thesoz)Institutionalismus; (thesoz)institutioneller Wandel; (thesoz)Determinismus; (thesoz)sozialer Wandel; (thesoz)politischer Wandel; Institutioneller Wandel (STW); Pfadabhängigkeit (STW); Bayes-Statistik (STW); Theorie (STW); Politische Entscheidung (STW); Arbeitspapier; Graue Literatur; Buch; Online-Publikation; Institutionalismus; Hysterese; Bayes-Regel; Theorie; Politische Entscheidung